PENINGKATAN KEMAMPUAN PENGUASAAN KOSAKATA BAHASA INDONESIA MELALUI METODE BERCERITA WAYANG KONTEMPORER KELAS A DI RA PLUS TUNAS ISLAM WANDANPURO BULULAWANG-MALANG - Khusnah, Jamilatul Khusnah; Nurhalimah, Evi (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2020)
The application of the method of storytelling using contemporary puppet media is very effective in practicing vocabulary mastery in children. The purpose of this research is to describe the improvement of Indonesian vocabulary mastery through storytelling using contemporary puppet media in class A. Action Research by applying two cycles through the process of planning, implementing, observing and reflecting. Data collection techniques are done by interview, observation, and documentation. The results of the assessment and discussion carried out through Cycle I and Cycle II focused on activities to recognize Indonesian vocabulary about nouns, verbs, adjectives, and adverbs with the final results of the success indicator process 22,2% to 64.77%. This study experienced an increase between cycles with a percentage of 43.48% with a moderate category that manifested the success in the use of contemporary puppet media to provide stimulus to the mastery of children's language vocabulary by telling stories.